2008
DOI: 10.1215/15228517-2008-013
|View full text |Cite
|
Sign up to set email alerts
|

Phase I safety study of escalating doses of atrasentan in adults with recurrent malignant glioma

Abstract: Atrasentan is an oral selective endothelin-A receptor antagonist that may inhibit cell proliferation and interfere with angiogenesis during glioma growth. We conducted a dose-finding study to assess atrasentan's safety and toxicity and to gather preliminary evidence of efficacy. Patients with recurrent malignant glioma received oral atrasentan at >or=10 mg/day. We increased the dose among cohorts until the maximum tolerated dose (MTD) was defined. Patients were evaluated for response every 8 weeks and remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This finding may help to explain the disappointing results from clinical trials of single agent endothelin receptor antagonists in cancer patients (21). For example, atrasentan produced only partial responses (8%) in a phase I trial in patients with recurrent glioblastoma (48). Combination studies of type-selective endothelin receptor antagonists with chemotherapy have also failed to demonstrate improved clinical benefit (49).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may help to explain the disappointing results from clinical trials of single agent endothelin receptor antagonists in cancer patients (21). For example, atrasentan produced only partial responses (8%) in a phase I trial in patients with recurrent glioblastoma (48). Combination studies of type-selective endothelin receptor antagonists with chemotherapy have also failed to demonstrate improved clinical benefit (49).…”
Section: Discussionmentioning
confidence: 99%
“…Atrasentan (ABT-627) is an ETA receptor selective antagonist currently being investigated for new drugs in the arsenal of brain tumor therapy. Atrasentan has shown promising results in its ability to inhibit tumor cell proliferation and angiogenesis (Phuphanich et al 2008 ) . Given that the ET receptors and peptides are known to be expressed throughout much of the brain, further investigation is necessary to explore the potential gain from pharmacological manipulation in the treatment of brain-related diseases.…”
Section: Brainmentioning
confidence: 99%
“…A Phase I‐II study of atrasentan in combination with paclitaxel and carboplatin in chemotherapy‐naïve patients with stage IIIB and IV NSCLC reported that this combination was well tolerated, and efficacy (Response Evaluation Criteria In Solid Tumors) and median survival were comparable with chemotherapy alone (Chiappori et al ., 2008). Atrasentan has also been investigated in a Phase I safety study in patients with progressive or recurrent malignant glioma (Phuphanich et al ., 2008), and in a Phase II trial of patients with locally recurrent or metastatic kidney cancer, data from which did not support further investigation as monotherapy in this patient population (Manola et al ., 2007).…”
Section: Targeting the Et Axis As An Anticancer Approachmentioning
confidence: 99%